Description of the first instar larva of Lytta caraganae (Pallas, 1798) (Coleoptera: Meloidae, Lyttini) - Li, Xiu-Min; Ren, Guo-Dong; Pan, Zhao (Zootaxa, 2019)
Lytta caraganae (Pallas, 1798) is widely distributed in northeast Asia. Its first instar larva hatched from eggs is described and illustrated using scanning electron microscopy (SEM). An update key to the all Lytta species based on first instar larvae is presented.